Activation and Genetic Modification of Human Monocyte-Derived Dendritic Cells using Attenuated Salmonella typhimurium - Agnieszka Michael; Justin John; Brendan Meyer; Hardev Pandha (The Scientific World Journal)
Live attenuated bacterial vectors, such as Salmonella typhimurium, have shown promise as delivery vehicles for DNA. We have examined two new strains of S. typhimurium and their impact on dendritic cell maturation (CD12-sifA/aroC mutant and WT05-ssaV/aroC, both in TML background). Strain WT05 matured dendritic cells in a more efficient way; caused higher release of cytokines TNF-α, IL-12, IL-1β; and was efficient for gene transfer. These findings suggest that the genetic background of the attenuation can influence the pattern of inflammatory immune response to Salmonella infection.